Déplacements domicile-travail : état des lieux et perspectives d’action pour les entreprises - Thomas Ermans; Céline Brandeleer; Michel Hubert; Kevin Lebrun; Florentine Sieux (Brussels Studies, 2018)
Travel between home and work structures the daily life of many workers in Belgium. How is this mobility organised and what are the factors which influence the modal choice of workers? What are the levers which influence this choice and, in particular, what is the role of companies in this area? The objective of this synopsis is to review the current situation of these complex questions and it is organised in three parts: the context of these journeys, the evolution of mobility behaviour and its deciding factors, and the levers for action in order to evolve towards more sustainable mobility. This synopsis also shows that travel between home and work is not only a transport issue, but is also related to people’s residential situation and land use planning. The latter suffers because of the institutional division of Belgium and calls for more coherence and dialogue among stakeholders. Despite this context, companies have significant room for manoeuvre, which this synopsis illustrates through three areas for action: the organisation of work, the management of the mobility of workers and accessibility.